Illness Perception Profiles and Their Association with 10-Year Survival Following Cardiac Valve Replacement. Issue 5 (20th February 2015) - Crawshaw, Jacob; Rimington, Helen; Weinman, John; Chilcot, Joseph
Abstract: Objective: The aim of the present study was to examine whether profiles of illness perceptions are associated with 10-year survival following cardiac valve replacement surgery. Methods: Illness perceptions were evaluated in 204 cardiac patients awaiting first-time valve replacement and again 1 year post-operatively using cluster analysis. All-cause mortality was recorded over a 10-year period. At 1 year, 136 patients were grouped into one of four profiles (stable positive, stable negative, changed from positive to negative, changed from negative to positive). Results: The median follow-up was 3063 days (78 deaths). After controlling for clinical covariates, including markers of function, patients who changed illness perceptions from positive to negative beliefs 1 year post-surgery had an increased mortality risk (hazard ratio (HR) = 3.2, 95 % confidence interval (CI) 1.2–8.3, p = .02) compared to patients who held positive stable perceptions. Conclusions: Following cardiac valve replacement, developing negative illness perceptions over the first post-operative year predicts long-term mortality. Early screening and intervention to alter this pattern of beliefs may be beneficial.